Women's orgasm obstacles: A qualitative study - Maryam Nekoolaltak; Zohreh Keshavarz; Masoumeh Simbar; Ali Mohammad Nazari; Ahmad Reza Baghestani (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Woman’s orgasm plays a vital role in sexual compatibility and marital satisfaction. Orgasm in women is a learnable phenomenon that is influenced by several factors. Objective: The aim of this study is exploring obstacles to orgasm in Iranian married women. Materials and Methods: This qualitative study with directed content analysis approach was conducted in 2015-2016, on 20 Iranian married women who were individually interviewed at two medical clinics in Tehran, Iran. Results: Orgasm obstacles were explored in one category, 4 subcategories, and 25 codes. The main category was “Multidimensionality of women’s orgasm obstacles”. Subcategories and some codes included: Physical obstacles (wife’s or husband’s boredom, vaginal infection, insufficient vaginal lubrication), psychological obstacles (lack of sexual knowledge, shame, lack of concentration on sex due to household and children problems), relational obstacles (husband’s hurry, having a dispute and annoyance with spouse) and contextual obstacles (Irregular sleep hours, lack of privacy and inability to separate children’s bedroom from their parents, lack of peace at home). Conclusion: For prevention or treatment of female orgasm disorders, attention to physical factors is not enough. Obtaining a comprehensive history about physical, psychological, relational and contextual dimensions of woman’s life is necessary.